2017
DOI: 10.2147/ppa.s152579
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after switching from warfarin to apixaban in patients with nonvalvular atrial fibrillation: AGAIN study

Abstract: PurposePatients treated with warfarin must adhere to frequent monitoring, dietary restrictions, and complicated dose adjustments. Apixaban, a direct factor Xa inhibitor, is an alternative to warfarin that may reduce patient burdens associated with warfarin therapy. However, there is limited evidence pertaining to patient satisfaction with anticoagulant therapies in Japanese patients. The purpose of this observational study was to investigate changes in patient satisfaction after switching from warfarin to apix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Of the 6 controlled trials, 5 were conducted in multiple countries (including UK, USA, Canada, Netherlands, France, Germany and Italy) [23][24][25]40,41 and 1 was conducted in Japan. 26 The observational studies (n = 15) used the following study designs: 11 prospective studies conducted in Spain, France, Canada, Japan, USA, Australia and Europe. Four of the studies were cross-sectional studies conducted in Spain, France and Canada (see Table 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 6 controlled trials, 5 were conducted in multiple countries (including UK, USA, Canada, Netherlands, France, Germany and Italy) [23][24][25]40,41 and 1 was conducted in Japan. 26 The observational studies (n = 15) used the following study designs: 11 prospective studies conducted in Spain, France, Canada, Japan, USA, Australia and Europe. Four of the studies were cross-sectional studies conducted in Spain, France and Canada (see Table 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…In the case of controlled trials, 5 studies used randomized methods to generate the sequence, 23,24,26,40,41 and 1 study used some form of data checking for patient selection (see Table 2). 25 However, only 3 studies clearly described a form of concealed allocation and personnel and participant blinding.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…The use of a therapy associated with higher satisfaction is a critical issue, due to its relationship to treatment adherence, 55,56 associated better anticoagulation control, 46 and consequently improved health outcomes. 49,57 Moreover, optimal adherence is essential to ensure both efficacy and safety with anticoagulant therapy and adherence to OACs remains a challenge in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Some did not demonstrate or report that dissatisfaction from previous NOAC or VKA treatment was not present at the start. 14,33,[44][45][46][47] Additionally, in some studies the outcome was assessed by nonblinded interviewers. 40,41,43,48,49 Moreover, in three studies there may be bias regarding the patients lost to follow-up.…”
Section: Risk Of Biasmentioning
confidence: 99%
“… 14 20 Although many patients with nonvalvular AF (NVAF) have switched to DOAC therapy, a significant proportion of patients are still treated with warfarin. The AGAIN study 38 was a prospective observational study conducted in Japanese patients with NVAF that investigated patient-reported satisfaction with apixaban after switching from warfarin (UMIN000018970). In this study, most physicians switched patients to apixaban in compliance with treatment guidelines, 21 but many patients remained on warfarin for reasons unsubstantiated by scientific evidence, including higher prices of DOACs compared to warfarin, lack of pressing reasons to switch (INR stably controlled within the therapeutic range), and fear of the potential risks of bleeding or ischemic events during the transition, either due to an overlap or a gap between warfarin and DOAC coverage.…”
Section: Introductionmentioning
confidence: 99%